D. FROUD, H. HARRISS (eds.) - Radical Pedagogies: Architectural Education and the British Tradition - Griffiths, Gareth (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Daisy Froud and Harriet Harriss (eds.) Radical Pedagogies: Architectural Education and the British Tradition London: RIBA Publishing, 2015, 304 pages. Language: English. 43 €. ISBN: 9781859465837